Stability of rarefaction wave for isentropic compressible Navier–Stokes–Maxwell equations. (June 2021) - Luo, Fangqi; Yao, Huancheng; Zhu, Changjiang
Abstract: We study the large-time asymptotic behavior of solutions toward the weak rarefaction wave of Navier–Stokes equations coupling with the Maxwell equations under small perturbations of initial data and also under the dielectric constant suitably small. The result is proved based on elementary L 2 energy methods.